Analisis Kenaikan Harga Emas di Pegadaian Baturaja 5 Tahun Terakhir (2020-2025) - Reny Shinta Sari (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
Gold is one of the most preferred investment instruments due to its relatively stable economic value and its function as a safe haven asset. This study aims to analyze the trend of gold prices at Pegadaian Baturaja over the last five years up to the most recent period and to examine the effect of gold price changes on customer behavior in utilizing gold-based financial services. This research employs a descriptive quantitative method with a trend analysis approach. The data were obtained from Pegadaian gold price data presented in five-year trend graphs, as well as primary data collected through observation and direct interviews conducted by Setiya on October 18, 2025. The results indicate that gold prices at Pegadaian Baturaja show an increasing trend. The increase in gold prices has a positive effect on customer interest in gold pawn services, gold savings, and gold installment products. The relationship between gold prices and customer behavior demonstrates a positive linear pattern, where an increase in gold prices is followed by an increase in demand for gold-based financial services